Respostas
respondido por:
19
segue os calculos em anexo, qualquer coisa pergunta ai
Anexos:
respondido por:
25
Oi
sen(7pi/2) = sen(7pi/2 - 8pi/2) = sen(-pi/2) = -sen(pi/2) = -1
cos(31pi) = cos(32pi - 31pi) = cos(pi) = -1
sen(7pi/2)*cos(31pi) = (-1)*(-1) = 1
.
sen(7pi/2) = sen(7pi/2 - 8pi/2) = sen(-pi/2) = -sen(pi/2) = -1
cos(31pi) = cos(32pi - 31pi) = cos(pi) = -1
sen(7pi/2)*cos(31pi) = (-1)*(-1) = 1
.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás